The formation and evolution of galaxies as a function of environment - Jaffe, Yara Lorena (2012)
This thesis investigates the role of environment on galaxy formation and evolution, giving particular focus to the transformation of star forming spirals into passive S0s. The data utilised for this study comes from photometric and spectroscopic observations of galaxies at 0 < z < 1 in different environments from the ESO Distant Cluster Survey. We first study the formation history of (172) cluster ellipticals (Es) and S0s, the oldest types of galaxies in the local universe. We examine their colour-magnitude relation (CMR), and find a very small intrinsic colour scatter. Only 7% of the galaxies are significantly bluer than the CMR. The scarcity of blue S0s indicates that, if they are the descendants of spirals, these were already red when they became S0s. We observe no dependence of the CMR scatter with z or cluster velocity dispersion. This implies that by the time cluster E/S0s achieve their morphology, the vast majority have already joined the red sequence. We estimate the galaxy formation redshift z_F for each cluster and find that while it does not depend on the cluster velocity dispersion, it increases weakly with cluster redshift. This suggests that, at any given z, in order to have a population of fully-formed E and S0s they needed to have formed most of their stars ≃2–4Gyr prior to observation. In other words, the galaxies that already have early-type morphologies also have reasonably-old stellar populations. This is partly a manifestation of the "progenitor bias", but also a consequence of the fact that the vast majority of the E/S0s in clusters (in particular the massive ones) were already red by the time they achieved their morphology. Moreover, E and S0 galaxies exhibit very similar colour scatter, implying similar stellar population ages. We also find that fainter E/S0s finished forming their stars later, consistent with the cluster red sequence being built over time and the brightest galaxies reaching the red sequence earlier than fainter ones. Finally, we find that the E/S0s cluster galaxies must have had their star formation truncated over an extended period ∆t ≿1 Gyr.